1997
DOI: 10.1111/j.1524-4725.1997.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Manual Resurfacing and Trichloroacetic Acid for the Treatment of Patients with Widespread Actinic Damage

Abstract: The deeper level of this peel explains the improved cosmetic outcome and greater eradication of actinic keratoses. This treatment is particularly well suited for patients with extensive photodamage and widespread actinic keratoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Whereas TCA peeling is an extensively performed procedure in aesthetic dermatology to reverse signs of photodamage, its role in treating AKs is as yet poorly delineated . As a consequence, chemical peels are in general mentioned only briefly or even omitted completely from current treatment recommendations for AK and field cancerization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas TCA peeling is an extensively performed procedure in aesthetic dermatology to reverse signs of photodamage, its role in treating AKs is as yet poorly delineated . As a consequence, chemical peels are in general mentioned only briefly or even omitted completely from current treatment recommendations for AK and field cancerization.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas TCA peeling is an extensively performed procedure in aesthetic dermatology to reverse signs of photodamage, 14 its role in treating AKs is as yet poorly delineated. [19][20][21][22][23] As a consequence, chemical peels are in general mentioned only briefly 24,25 or even omitted completely from current treatment recommendations 26 for AK and field cancerization. In theory, TCA peeling appears to be a promising therapeutic approach for AK as, like PDT, it allows for treating large skin areas in a single therapeutic session and at the same time may improve the appearance of chronically photodamaged skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies 14,15,[17][18][19] have shown that resurfacing of the face can prevent or delay the occurrence of these lesions, especially in high-risk patients. We compared 2 skin resurfacing regimens, carbon dioxide laser resurfacing and 30% trichloroacetic acid peel, with topical 5% fluorouracil cream to determine whether any modality was superior for AK reduction and skin cancer prevention during a 5-year study.…”
Section: T He Risk Of An Individualmentioning
confidence: 99%
“…The nonblinded right/left comparison by Witheiler et al 24 of a 35% TCA peel and 5‐FU on the face suggested that they were of similar efficacy, with improvement sustained up to 12 months, waning considerably by 32 months. TCA can be combined with 70% glycolic acid 48 or with manual dermabrasion with silicon carbide sandpaper 49 …”
Section: Other Treatmentsmentioning
confidence: 99%